A large therian mammal from the Late Cretaceous of South America - Chimento, Nicolás Roberto (2024)
Theria represent an extant clade that comprises placental and marsupial mammals. Here we report on the discovery of a new Late Cretaceous mammal from southern Patagonia, Patagomaia chainko gen. et sp. nov., represented by hindlimb and pelvic elements with unambiguous therian features. We estimate Patagomaia chainko attained a body mass of 14 kg, which is considerably greater than the 5 kg maximum body mass of coeval Laurasian therians. This new discovery demonstrates that Gondwanan therian mammals acquired large body size by the Late Cretaceous, preceding their Laurasian relatives, which remained small-bodied until the beginning of the Cenozoic. Patagomaia supports the view that the Southern Hemisphere was a cradle for the evolution of modern mammalian clades, alongside non-therian extinct groups such as meridiolestidans, gondwanatherians and monotremes.